Is gender crucial for cardiovascular adjustments induced by exercise training in female spontaneously hypertensive rats? - Coimbra, Rosemeire; Sanchez, Lylian S.; Potenza, Janaina M.; Rossoni, Luciana V.; Amaral, Sandra Lia [UNESP]; Michelini, Lisete C. (Lippincott Williams & Wilkins, 2008)
Evidence of mild hypertension in women and female rats and our preliminary observation showing that training is not effective to reduce pressure in female as it does in male spontaneously hypertensive rats (SHR) prompt us to investigate the effects of gender on hemodynamic pattern and microcirculatory changes induced by exercise training. Female SHR and normotensive controls (Wistar- Kyoto rats) were submitted to training (55% VO2 peak; 3 months) or kept sedentary and instrumented for pressure and hindlimb flow measurements at rest and during exercise. Heart, kidney, and skeletal muscles (locomotor/ nonlocomotor) were processed for morphometric analysis of arterioles, capillaries, and venules. High pressure in female SHR was accompanied by an increased arteriolar wall: lumen ratio in the kidney (+30%; P < 0.01) but an unchanged ratio in the skeletal muscles and myocardium. Female SHR submitted to training did not exhibit further changes on the arteriolar wall: lumen ratio and pressure, showing additionally increased hindlimb resistance at rest (+29%; P < 0.05). on the other hand, female SHR submitted to training exhibited increased capillary and venular densities in locomotor muscles (+50% and 2.3- fold versus sedentary SHR, respectively) and normalized hindlimb flow during exercise hyperemia. Left ventricle pressure and weight were higher in SHR versus WKY rats, but heart performance (positive dP/dt(max) and negative dP/dt(max)) was not changed by hypertension or training, suggesting a compensated heart function in female SHR. In conclusion, the absence of training- induced structural changes on skeletal muscle and myocardium arterioles differed from changes observed previously in male SHR, suggesting a gender effect. This effect might contribute to the lack of pressure fall in trained female SHRs.
Keywords: skeletal muscle; myocardium; kidney; arterioles; capillaries; venules; vascular resistance